2021
DOI: 10.1101/2021.12.23.474039
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiplex, translaminar imaging in the spinal cord of behaving mice

Abstract: While the spinal cord is known to play critical roles in sensorimotor processing, including pain-related signaling, corresponding activity patterns in genetically defined cell types across spinal laminae have remained elusive. Calcium imaging has enabled cellular activity measurements in behaving rodents but is currently limited to superficial regions. Using chronically implanted microprisms, we imaged sensory and motor evoked activity in regions and at speeds inaccessible by other high-resolution imaging tech… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Recent studies have also indicated that spinal cord astrocytes are regionally heterogeneous (Kronschläger et al, 2021; Molofsky et al, 2014; Shekhtmeyster, Carey, et al, 2021), that this heterogeneity is functionally relevant (Kelley et al, 2018; Kohro et al, 2020) and associated with distinct spatiotemporal excitation patterns. For example, using translaminar imaging in behaving mice with chronically implanted microprisms, astrocytes in sensory and premotor areas of the spinal dorsal horn were found to respond to noxious mechanical stimuli and locomotion in a lamina‐specific manner (Shekhtmeyster, Carey, et al, 2021). In contrast, Tac1‐expressing neurons, involved in pain processing, responded to the same noxious stimuli with calcium spiking in sensory regions but did not respond to locomotion, suggesting that lamina‐specific astrocyte activity depends on the neuronal cell type.…”
Section: Relating Astrocyte Functions To Neural Circuit Operation And...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have also indicated that spinal cord astrocytes are regionally heterogeneous (Kronschläger et al, 2021; Molofsky et al, 2014; Shekhtmeyster, Carey, et al, 2021), that this heterogeneity is functionally relevant (Kelley et al, 2018; Kohro et al, 2020) and associated with distinct spatiotemporal excitation patterns. For example, using translaminar imaging in behaving mice with chronically implanted microprisms, astrocytes in sensory and premotor areas of the spinal dorsal horn were found to respond to noxious mechanical stimuli and locomotion in a lamina‐specific manner (Shekhtmeyster, Carey, et al, 2021). In contrast, Tac1‐expressing neurons, involved in pain processing, responded to the same noxious stimuli with calcium spiking in sensory regions but did not respond to locomotion, suggesting that lamina‐specific astrocyte activity depends on the neuronal cell type.…”
Section: Relating Astrocyte Functions To Neural Circuit Operation And...mentioning
confidence: 99%
“…To date, most spinal cord studies involving astrocytes have been performed in reduced preparations or anesthetized animals, mainly due to the technical difficulty of obtaining stable recordings from this CNS region during animal behavior, which typically results in large amplitude and nonlinear tissue displacements ( Nelson et al., 2019 ). The few studies that have been conducted in awake mice demonstrate that anesthesia powerfully suppresses spinal neuron and astrocyte activity and that sensorimotor-driven astrocyte excitation is complex and regionally heterogeneous ( Sekiguchi et al, 2016 ; Shekhtmeyster, Carey, et al, 2021 ; Shekhtmeyster, Duarte, et al, 2021 ). For example, using quantitative sensory and motor assays together with in vivo calcium imaging, superficial (i.e., lamina I–II) dorsal horn astrocytes were found to respond to innocuous sensory stimuli (tail pinch) with asynchronous increases in the frequency but not amplitude or duration of their microdomain transients.…”
Section: Relating Astrocyte Functions To Neural Circuit Operation And...mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, miniscopes have also enabled real-time measurement of cellular activity in the spinal cord of behaving mice. 372,[377][378][379] In the future, we can expect these imaging systems to become even more powerful. Improved electronics and optics (e.g., new CMOS sensors, custom micro-optics, electronic focusing systems) will enhance 1P miniscopes' ability to record at higher resolution, sensitivity, contrast, and speed, in multiple colors and across larger FOVs or tissue volumes.…”
Section: Wearable 1p Microscopesmentioning
confidence: 99%
“…Improved electronics and optics (e.g., new CMOS sensors, custom micro-optics, electronic focusing systems) will enhance 1P miniscopes' ability to record at higher resolution, sensitivity, contrast, and speed, in multiple colors and across larger FOVs or tissue volumes. 352,372,[378][379][380] While initial tether-free designs exist [Fig. 19(a)], further improvements in onboard or wireless power and data transmission technology are needed to reduce overall device weight and boost recording duration at desired image resolutions and frame rates.…”
Section: Wearable 1p Microscopesmentioning
confidence: 99%